1999
DOI: 10.1097/00004728-199903000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Air Trapping in Primary Sjögren Syndrome: Correlation of Expiratory CT with Pulmonary Function Tests

Abstract: Expiratory high resolution CT revealed the extent of bronchiolar disease in patients with primary Sjögren syndrome. We also found that the extent of air trapping did not correlate with PFTs, which suggests the existence of a subclinical bronchiolar inflammatory process that may precede detectable abnormalities in lung function tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 15 publications
0
23
1
Order By: Relevance
“…Other authors reported a mixed ventilatory defect [41] or a relatively high frequency of small airways obstruction [4]. In another study [34] all the patients with findings of air trapping on thin-section CT scans had normal PFT results, and the extent of air trapping did not correlate with PFT. The authors of that study concluded that air trapping can be an early marker of disease, and may develop earlier than impairment of lung function.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Other authors reported a mixed ventilatory defect [41] or a relatively high frequency of small airways obstruction [4]. In another study [34] all the patients with findings of air trapping on thin-section CT scans had normal PFT results, and the extent of air trapping did not correlate with PFT. The authors of that study concluded that air trapping can be an early marker of disease, and may develop earlier than impairment of lung function.…”
Section: Discussionmentioning
confidence: 88%
“…6a, b Transverse thin-section CT scans of the lungs from a 76-year-old woman with PSS and ILF shows diffuse ground-glass attenuation with multiple randomly distributed thin-walled lung cysts. Mild septal and intralobular thickening is also present The results are expressed as percentages of the normal predicted values (mean±SD) The 2 patients with normal scans and the 2 patients with findings or images suggestive of pulmonary hypertension were excluded PSS patients [5,10,34], leading to an increased risk of recurrent respiratory tract infections in association with tracheal and bronchial dryness [4,35], Airway disease is defined as bronchial wall thickening and/or bronchiectasis when the large airways are involved and findings of cellular and constrictive bronchiolitis when the small airways are affected [36]. Franquet et al reported CT abnormalities of the small airways in 11 of 34 (32%) of patients [34].…”
Section: Pft-ct Findings Correlationmentioning
confidence: 99%
“…Both follicular bronchiolitis and constrictive bronchiolitis may be encountered in subjects with connective tissue diseases and may even coexist in the same patient [41,44]. CT scan findings in Sjö gren's syndrome and in rheumatoid arthritis have been the subject of many studies [44][45][46][47][48][49][50][51][52][53][54], and are characterised by usual signs of small airways abnormalities, including mosaic attenuation on inspiratory CT, air trapping on expiratory CT, ground-glass opacities, and centrilobular nodules eventually with tree-in-bud pattern (especially in cellular bronchiolitis) or distension (especially in constrictive bronchiolitis). CT scans may have better sensitivity than pulmonary function tests in rheumatoid arthritis [52].…”
Section: Connective Tissue Diseasesmentioning
confidence: 99%
“…In patients with both pSS and pSS, 22% had chest radiography abnormalities, with linear and reticular opacities being the most frequent finding [15]. HRCT findings in SS include both interstitial and airway abnormalities and both ILD and bronchiolar inflammatory changes are common abnormal findings seen in pSS [15,34,35,54]. Koyama et al reviewed chest HRCT findings of 60 patients with pSS and showed that the most common findings were ground-glass opacities (92%), centrilobular nodules (78%), nonseptal linear opacities (75%), interlobular septal thickening (55%), bronchiectasis (38%), and cysts (30%) [35].…”
Section: Radiological Featuresmentioning
confidence: 99%